Striated muscle activator of Rho signalling (STARS) is a PGC-1α/oestrogen-related receptor-α target gene and is upregulated in human skeletal muscle after endurance exercise - Wallace, Marita A (Blackwell Science Inc, 2011)
ABSTRACT: The striated muscle activator of Rho signalling (STARS) is an actin-binding protein specifically expressed in cardiac, skeletal and smooth muscle. STARS has been suggested to provide an important link between the transduction of external stress signals to intracellular signalling pathways controlling genes involved in the maintenance of muscle function. The aims of this study were firstly, to establish if STARS, as well as members of its downstream signalling pathway, are upregulated following acute endurance cycling exercise; and secondly, to determine if STARS is a transcriptional target of peroxisome proliferator-activated receptor gamma co-activator 1-α (PGC-1α) and oestrogen-related receptor-α (ERRα). When measured 3 h post-exercise, STARS mRNA and protein levels as well as MRTF-A and serum response factor (SRF) nuclear protein content, were significantly increased by 140, 40, 40 and 40%, respectively. Known SRF target genes, carnitine palmitoyltransferase-1β (CPT-1β) and jun B proto-oncogene (JUNB), as well as the exercise-responsive genes PGC-1α mRNA and ERRα were increased by 2.3-, 1.8-, 4.5- and 2.7-fold, 3 h post-exercise. Infection of C2C12 myotubes with an adenovirus-expressing human PGC-1α resulted in a 3-fold increase in Stars mRNA, a response that was abolished following the suppression of endogenous ERRα. Over-expression of PGC-1α also increased Cpt-1β, Cox4 and Vegf mRNA by 6.2-, 2.0- and 2.0-fold, respectively. Suppression of endogenous STARS reduced basal Cpt-1β levels by 8.2-fold and inhibited the PGC-1α-induced increase in Cpt-1β mRNA. Our results show for the first time that the STARS signalling pathway is upregulated in response to acute endurance exercise. Additionally, we show in C2C12 myotubes that the STARS gene is a PGC-1α/ERRα transcriptional target. Furthermore, our results suggest a novel role of STARS in the co-ordination of PGC-1α-induced upregulation of the fat oxidative gene, CPT-1β.